2014
DOI: 10.1016/j.jdmm.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Terrorism, rugby, and hospitality: She׳ll be right

Abstract: In 2011, international attention was focussed on New Zealand, host of the Rugby World Cup (RWC 2011), which brought 133,200 visitors to New Zealand over a three-month period. This exploratory study, undertaken before the event, investigates the attitudes of hotel managers and staff as they prepared to host spectators, rugby teams, and media personnel. The aim of the study was to determine preparedness for an attack, and assess attitudes and approaches to risk management in relation to terrorism. Interview data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
(61 reference statements)
0
13
0
Order By: Relevance
“…Pizam (2010) found that 30% of U.S. hotel general managers admitted that they had done nothing with regard to security procedures, and more than half thought that their security was sufficient. Peter et al (2014) investigated the attitudes of hotel managers and staff to risk management prior to the event in New Zealand. Chan (2004) clearly showed that gaps might exist between the perceptions of hotel management and hotel guests and that these gaps might affect guest satisfaction.…”
Section: Safety and Security Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…Pizam (2010) found that 30% of U.S. hotel general managers admitted that they had done nothing with regard to security procedures, and more than half thought that their security was sufficient. Peter et al (2014) investigated the attitudes of hotel managers and staff to risk management prior to the event in New Zealand. Chan (2004) clearly showed that gaps might exist between the perceptions of hotel management and hotel guests and that these gaps might affect guest satisfaction.…”
Section: Safety and Security Researchmentioning
confidence: 99%
“…1. Hotels have a long history of being a -soft target‖ environment for safety and security threats (Enz, and Taylor, 2002;Enz, 2009;Homeland Security, 2010;AlBattat, and Som, 2013;Chan, and Lam, 2013;Paraskevas, 2013;Lisle, 2013;Peter, et al, 2014). Hotel as a working environment have become an easy target because of several factors, including open access with 24 hours a day, many public and multiple access points, parking lots, and encounters with strangers and foreigners.…”
Section: Hotels Vulnerability To Safety and Security Threats And Hazardsmentioning
confidence: 99%
See 3 more Smart Citations